Design of braided fibrous structure (scaffold) for treatment of spinal injury using Rhinoceros 3D® software and Grasshopper plugin - Aguiar Souza, Ivis (2024)
Parametric design operates as an indispensable mechanism for the fabrication of elaborate geometries. In recent years, there has been an increase in the incidence of injuries to the spine and spinal cord. The most common causes of spinal cord injuries are traffic accidents, falls, high-impact sports, and acts of violence. The objective of this work was to graphically develop braided textile structures suitable for assisting in the treatment of spinal cord injuries. They were selected by criteria of number of layer yarns (internal and external), angle, structural diameter, and porosity. Thus, the structures have an internal layer with 8 yarns and an external layer with 8 or 16 yarns. The main requirement to select them is porosity of structure, and two main structures with different morphologies were simulated, followed by their characterization. The internal layer demonstrated a porosity of 84.77%, indicating feasibility for implementation. The external layer, one with 8 yarns, presented 82.14% porosity, similar to the previous sample, while the other with 16 yarns showed 66.03%. Both options exhibited clear distinctions: a conclusive framework comprising 8 strands in each layer manifested increased porosity, potentially compromising mechanical resilience. Conversely, a setup featuring 8 yarns in the internal layer and 16 in the external layer may confer enhanced mechanical attributes without compromising porosity. The utilization of Rhinoceros 3D software in collaboration with the Grasshopper plugin streamlined the morphological assessment process, facilitating the discernment of critical features prior to physical fabrication.